Elastocaloric cooling of additive manufactured shape memory alloys with large latent heat. (12th September 2017) - Hou, Huilong; Simsek, Emrah; Stasak, Drew; Hasan, Naila Al; Qian, Suxin; Ott, Ryan; Cui, Jun; Takeuchi, Ichiro
Abstract: The stress-induced martensitic phase transformation of shape memory alloys (SMAs) is the basis for elastocaloric cooling. Here we employ additive manufacturing to fabricate TiNi SMAs, and demonstrate compressive elastocaloric cooling in the TiNi rods with transformation latent heat as large as 20 J g −1 . Adiabatic compression on as-fabricated TiNi displays cooling Δ T as high as  −7.5 °C with recoverable superelastic strain up to 5%. Unlike conventional SMAs, additive manufactured TiNi SMAs exhibit linear superelasticity with narrow hysteresis in stress–strain curves under both adiabatic and isothermal conditions. Microstructurally, we find that there are Ti2 Ni precipitates typically one micron in size with a large aspect ratio enclosing the TiNi matrix. A stress transfer mechanism between reversible phase transformation in the TiNi matrix and mechanical deformation in Ti2 Ni precipitates is believed to be the origin of the unique superelasticity behavior.